The cascade of care for Australians living with chronic hepatitis B: measuring access to diagnosis, management and treatment - Nicole L. Allard; Jennifer H. MacLachlan; Benjamin C. Cowie (Elsevier, 2015)
Abstract Objective: To estimate the level of access to diagnosis, management and treatment for people living with chronic hepatitis B (CHB) in Australia, and to identify the gaps in clinical care for people living with CHB. Methods: Analysis of publicly available population level data including infectious disease notifications, Medicare and Pharmaceutical Benefits Scheme utilisation data, census‐based estimates of CHB prevalence and burden, and mathematical modelling. Results: In 2012, of the estimated 218,567 Australians living with CHB, 57% had been diagnosed, 17,367 people (8%) received recommended HBV DNA viral load testing (without treatment) and 10,987 (5%) received antiviral therapy. Conclusions: This analysis reveals substantial gaps in the cascade of care for CHB in Australia, most notably in diagnosis (with 43% undiagnosed) and in recommended yearly monitoring (87% not in care). The number receiving therapy represents only one‐third of those estimated to require treatment to prevent progressive liver disease and liver cancer. Implications: These findings demonstrate that the majority of those affected are not receiving guideline‐based care; highlight the need for improvements in opportunistic screening, engagement in care, and access to therapy; and provide a method to assess the impact of public health and clinical interventions in response to CHB over time.